2015
DOI: 10.1364/oe.23.018955
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability to ciphertext-only attack of optical encryption scheme based on double random phase encoding

Abstract: We demonstrate in this paper that the traditional double random phase encoding (DRPE) technique is vulnerable to ciphertext-only attack (COA). In this method, an unauthorized user (or say attacker) is assumed to be able to retrieve the corresponding plaintext from the only ciphertext under some certain condition. The proposed scheme mainly relies on a hybrid iterative phase retrieval (HIPR) algorithm, which combines various phase retrieval algorithms. With an estimation of the number of nonzero pixels (NNP) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(28 citation statements)
references
References 43 publications
0
27
0
1
Order By: Relevance
“…Using the second one, a concentric-circle phase mask with a period of 75 µm (Figure 6d), an encoded FGI diffraction patterns as shown in Figure 6e was obtained, which is almost the same as the encoded diffraction pattern in Figure 6f obtained from the conventional coherent diffraction imaging simulation. Then the image can be reconstructed by utilizing phase retrieval algorithms with sparsity constraints [92][93][94][95][96][97][98][99][100][101]. Figure 6.…”
Section: X-ray Fourier-transform Giscmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the second one, a concentric-circle phase mask with a period of 75 µm (Figure 6d), an encoded FGI diffraction patterns as shown in Figure 6e was obtained, which is almost the same as the encoded diffraction pattern in Figure 6f obtained from the conventional coherent diffraction imaging simulation. Then the image can be reconstructed by utilizing phase retrieval algorithms with sparsity constraints [92][93][94][95][96][97][98][99][100][101]. Figure 6.…”
Section: X-ray Fourier-transform Giscmentioning
confidence: 99%
“…(2) h ∆r 0 2λz 1 . The object I 0 (r 0 ) can be reconstructed by utilizing phase retrieval algorithms with sparsity constraints [92][93][94][95][96][97][98][99][100][101]. In some cases, only amplitude information of an object is interested, which can be used as a constraint to greatly improve the reconstruction quality in phase retrieval [109].…”
Section: Lensless Wiener-khinchin Telescopementioning
confidence: 99%
“…Conversely, the cryptoanalysis can stimulate the development of more advantageous and secure schemes. Hence, cryptoanalysis of optical encryption schemes [29][30][31][32][33] is also of high importance. Carnicer et al [29] first reported that the DRPEbased optical encryption is vulnerable to chosen-ciphertext attack.…”
mentioning
confidence: 99%
“…Liao et al [32] analyzed optical encryption systems using ciphertextonly attack (COA) to retrieve the plaintext. Recently, Liu et al [33] improved the COA method by using multiple phase retrieval algorithms to develop a hybrid iterative phase retrieval algorithm. Conventional methods for analyzing the vulnerability of optical cryptosystems focused on applying elaborately-designed information to retrieve or estimate various optical encryption keys.…”
mentioning
confidence: 99%
“…Si se cumplen estas condiciones, ( , ) k o x y será una buena aproximación al texto plano, permitiendo al adversario adquirir la información encriptada sin necesidad adquirir las llaves de encriptación.La mayoría de los COA siguen una estrategia similar a la descrita anteriormente, y se diferencian principalmente en las ligaduras que usa el adversario a la hora de aplicar el algoritmo de reconstrucción de fase. Estas ligaduras pueden ser, adicionalmente al soporte del texto plano, el número de pixeles distintos de cero que compone el objeto[43]. Al igual que en los ataques KPA, una forma de dificultar este tipo de ataque en los sistemas JTC consiste en filtrar el JPS, ya que analizando los distintos órdenes que se encuentran en la TFI del JPS, es posible determinar el soporte y la geometría del plano de entrada, facilitando así el COA.…”
unclassified